Legal certainty on the claimed land as a forest area in the neighborhood of the Batulapisi district of Gowa - Pota, Al Araaf Ode; M.Pide, A. Suyaman; Susyanti Nur, Sri (Fakultas Hukum Universitas Widya Mataram, 2022)
This study examines the implications of land registration after the release of forest areas in the Batu Lapisi neighborhood in Malino Village, Tinggi Moncong District, Gowa Regency. The research conducted is empirical research. Empirical research examines law in action. Thus, the empirical world is das sein (what is the reality. Data analysis is descriptive by providing an overview of what should be done about these legal problems. The results show that the implementation of land registration which is claimed as a forest area in the Batu lapisi Dalam environment) Kelurahan Malino was implemented based on the recognition of old rights in the form of Ipeda evidence in 1976, then the National Agrarian Operations Project program in 1991 and finally the release of forest areas based on the Decree of the Minister of Environment and Forestry No. 362 / MENLHK / SETJEN / PLA.0/ 5 / 2019 with the method of land registration for the first time sporadically. Implications of land registration after area release is carried out under the authority of the Ministry of Environment and Forestry of the Republic of Indonesia which issues land parcels based on the Spatial Review scheme of conservation forest areas by issuing them a Decree of the Minister of Environment and Forestry No.362/MENLHK/SETJEN/PLA.0/ 5/2019, then the minister determines the people who receive the Blue SK as the basis for registering land rights. After that, the Gowa Regency BPN carried out the administrative process of sporadic land registration based on the Blue Decree from the Minister of Environment and Forestry as well as evidence of physical control from the lurah or village head. If the land to be registered borders a forest area, a clarification or recommendation must be requested from the Regional 7 Makassar Forest Area Consolidation Center (BPKH). Keywords: Legal Certainty, Rights, Land, Forests, Environment